2017
DOI: 10.1002/ejsp.2249
|View full text |Cite
|
Sign up to set email alerts
|

Choosing between conciliatory and oppositional leaders: The role of out‐group signals and in‐group leader candidates' collective action tactics

Abstract: In this paper, we examine the role of out‐group signals and in‐group leader tactics in the choice and evaluation of rival in‐group leader candidates. Study 1 found preference for a negotiating in‐group leader over an oppositional leader, mediated by perceived leader effectiveness and prototypicality. In Study 2, participants chose a leader who had received out‐group endorsement, and in Studies 3 and 4, participants chose a negotiating in‐group leader where the out‐group was prepared to negotiate and an opposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…In addition, a key reason for volatility in one group's tactics is that opponents' tactics change. For example, opponents who are increasingly illegitimate, threatening, and intransigent may spur group members to embrace more confrontational tactics themselves (Blackwood & Louis, 2017;Livingstone, Spears, Manstead, & Bruder, 2009). Three significant bodies of literature that have considered tactical changes in relation to changes in intergroup relations involve research on political solidarity, intergroup contact, and radicalization.…”
Section: Changes In Orientation To Other Groups Change Tacticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a key reason for volatility in one group's tactics is that opponents' tactics change. For example, opponents who are increasingly illegitimate, threatening, and intransigent may spur group members to embrace more confrontational tactics themselves (Blackwood & Louis, 2017;Livingstone, Spears, Manstead, & Bruder, 2009). Three significant bodies of literature that have considered tactical changes in relation to changes in intergroup relations involve research on political solidarity, intergroup contact, and radicalization.…”
Section: Changes In Orientation To Other Groups Change Tacticsmentioning
confidence: 99%
“…Another hypothesis to test is that activists' responses to failure depend upon what a pool of leadership candidates is offering. For example, Blackwood and Louis (2017) found that when groups in conflict perceived that the outgroup would not negotiate, a majority would vote for a confrontational leader; otherwise, a negotiator was preferred by voters. This supports a DIME dynamic, namely radicalization when conventional action fails.…”
Section: The Dime Model: Disidentification Innovation Moralizationmentioning
confidence: 99%
“…What kinds of tactics have worked in the past (Stuart, Thomas, Donaghue, & Russell, 2013)? How do we understand the signals sent by powerful out-groups regarding their own strategic considerations and likely response (Blackwood & Louis, 2017)? How might out-group actions, such as repression, inform our perceptions of legitimacy and illegitimacy, of justice and injustice, and thus shape responses (Drury, Cocking, Beale, Hanson, & Rapley, 2005; Drury & Reicher, 2000, 2009; Stott & Reicher, 1998)?…”
Section: Focusing or Refocusing On Group Processes Of Radicalizationmentioning
confidence: 99%
“…Finally, Jasper’s (2017) review of the literatures on leadership, narratives, and frames should remind us that in both fields, arguably—but perhaps even more so within the social psychology of collective action—the leadership processes and contests that are vital to collective action have been underresearched (see Blackwood & Louis, in press ; Reicher, Haslam, Platow, & Steffens, 2016 ). This deficit will become more glaring as we seek to theorize the relationship between macro- and microlevel factors (e.g., Górska et al, 2017 ) and to address the cultural contestation of frames (e.g., Chayinska et al, 2017 ).…”
Section: Exciting Synergies and Lessons To Learn For The Futurementioning
confidence: 99%